Physical activity and physical exercise in perinatal depression prevention: a Systematic review and Meta-analysis - Pacheco, Ana Beatriz Fonseca Modesto Alves (2019)
Trabalho Final do Mestrado Integrado em Medicina apresentado à Faculdade de Medicina